Quality of the record of data on fatal workplace injuries in Brazil - Adriana Galdino; Vilma Sousa Santana; Silvia Ferrite (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE To evaluate the quality of the data on fatal workplace injuries in Brazil, in the Mortality Information System (SIM) and the Information System of Notifiable Diseases (SINAN-AT), analyzing the spatial and temporal distribution between 2007 and 2012. METHODS We identified fields related to fatal workplace injuries, which were examined for completeness and the use of the "ignored" option. From the SIM, we extracted the records of deaths from external causes, which require the completing of the <acidtrab> field about their relation with work. From the SINAN, we analyzed the <evolution> field, which allows us to identify fatal cases among s severe workplace injuries. RESULTS In the SIM, from 469,121 records, the <acidtrab> field was left unfilled or filled as ignored in 84.2% of them; the Brazilian region with the highest proportion was the Northeast (79.1%), from which the state of Alagoas (94.4%) had the highest amount. There was a 5.5% decreasing trend between 2007 (86.6%) and 2012 (81.8%). Among the 251,681 records found in the SINAN-AT, 28.3% had unfilled or ignored responses for <evolution>, varying from 39.7% in 2007 to 23.2% in 2012, a 41.6% decrease. CONCLUSIONS The quality of the records on the fields of interest needed to identify fatal workplace injuries is poor in the SIM, but gradually improving. Recording quality was better for SINAN-AT, which has also been strongly getting better lately.